Photodetectors: Ultrahigh‐Sensitive Broadband Photodetectors Based on Dielectric Shielded MoTe2/Graphene/SnS2 p–g–n Junctions (Adv. Mater. 6/2019). Issue 6 (8th February 2019) - Li, Alei; Chen, Qianxue; Wang, Peipei; Gan, Yuan; Qi, Tailei; Wang, Peng; Tang, Fangdong; Wu, Judy Z.; Chen, Rui; Zhang, Liyuan; Gong, Youpin
Abstract : In article number1805656, Rui Chen, Liyuan Zhang, Youpin Gong, and co‐workers develop an h‐BN/MoTe2 /graphene/SnS2 /h‐BN van der Waals heterostructure to realize an ultrahigh‐sensitivity broadband (405–1550 nm) photodetector, due to its unique advantages for high‐efficiency light absorption and exciton dissociation. Graphene plays a key role in enhancing the sensitivity and broadening the spectral range, providing a viable approach toward future ultrahigh sensitivity and broadband photodetectors.